Effect of the complexity of the customs tax system on the tax effort - Jazmín González Aguirre; Alberto del Villar (Economies, 2022)
This paper empirically analyses the effects of the tax complexity and other elements, such as natural resource revenues, public expenditure, and the capacity of the statistical system, on the efficiency of Ecuadorian Customs Administration. For this purpose, the methodology used consists of modeling a stochastic production frontier whose estimation procedure is based on the maximum likelihood method for a data panel composed of six countries: Bolivia, Chile, Colombia, Ecuador, Peru, and Panama for the period from 2006 to 2017. The results of the study show that the countries whose tax system has a lower degree of complexity present a better level of revenue collected and tax effort as well as an improvement in the quality and dissemination of national statistical data. Furthermore, this paper provides evidence that the tax effort tends to decrease when the price of crude oil is on the rise.
Keywords: E62; F13; H21; H83; 330; customs; Ecuador; efficiency; international trade; Latin America; tax complexity; tax effort